Deconstructing the Question of Irish Identity - Corbett, Tony (ABEI Journal, 2002)
Eugene O’Brien. The Question of Irish Identity in the Writings of William Butler Yeats and James Joyce. Lewiston New York: Edwin Mellen Press, 2001.pp. 281. ISBN: 0-7734-8237-7